URGENSI ADMINISTRASI PUBLIK DALAM ISLAM : TINJAUAN MASLAHAH MURSALAH - Rahmat, Widya; Oktavia, Luci Afiani (​Institute for Researches and Community Services Universitas Muhammadiyah Palangkaraya, 2024)
Every aspect of a nation's life is heavily influenced and determined by the maintenance of its rule. Public administration, whether governmental, financial, military, or judicial, has existed since the era of Islamic civilization. In Islamic perspectives, government begins with literacy. As is well known, the majority of the Indonesian population is Muslim, and the Islamic regime plays a role in the development of Indonesia. This study attempts to explore more deeply about administration in Islamic concepts and its relevance to modern administrative practices. This research is a type of library study with a research approach using qualitative research methods. This research suggests that public administration in Islam emphasizes such principles as trust (faith), adl (justice), shura (consultation), and maslahah (kesejahteraan umum). Moreover, public leaders in Islam are expected to act with integrity, transparency, and accountability. The study concludes that Islamic public administration approaches can provide a strong and ethical framework for modern administrative practices, which focus not only on results but also on fair and dignified processes. The findings provide important insights for academics and practitioners in understanding and integrating Islamic values into contemporary public administration. The focus of the public administration that adopts the principle of Maslahah Mursalah is to good for the community. It is hoped that policies made with priority on justice, transparency, and participation can meet the needs of communities and enhance common well-being.